Pengembangan Alat Peraga Efek Rumah Kaca Untuk Menumbuhkan Keterampilan Proses Sains Siswa SMP Kelas VII Pada Tema Pemanasan Global - Yulianah, Yulianah; Leksono, Suroso Mukti; El Islami, R. Ahmad Zaky (PendIPA Journal of Science Education, 2025)
The purpose of this research is to create a greenhouse effect teaching tool in science learning on the themeof global warming to foster Science Process Skills (PPP) in students. The development model used is a 4-D development model which consists of four stages: define, design, develop, and disseminate. Productvalidation was carried out by science education experts and practitioner experts who showed the level ofproduct validity with a value of 86.18% included in the "excellent" category. The implementation of the useof greenhouse effect props was carried out by grade VII students at one of the junior high schools in SerangCity. The data of the student response questionnaire showed that the teaching aids were able to grow PPPwith a score of 80.37% with the "very good" category. The results of this study prove that the use of teachingaids in science learning on the theme of global warming can help grow students' PPP through practicumactivities.